REDUCTION OF REAL POWER LOSS BY IMPROVED QUANTUM ALGORITHM - Lenin, K. (International Journal of Research -GRANTHAALAYAH, 2017)
In this paper, combination of the Q-bit evolutionary search - quantum particle swarm optimization (QPSO) algorithm and binary bit evolutionary search - genetic particle swarm optimization (GPSO) has been done to solve the reactive power problem & termed as Improved Quantum Algorithm (IQA). Proposed IQA can be viewed as a kind of hybridization of micro-space based search and macro-space based search, which augments the penetrating behavior to augment and balance the exploration and exploitation aptitudes in the whole searching space. In order to evaluate the performance of the proposed IQA algorithm, it has been tested on IEEE 57,118 bus systems and compared to other standard algorithms.